McCarthyism in the Suburbs : Quakers, Communists, and the Children's Librarian - Hepler, Allison (Lexington Books, 2018)
This study examines the effects of McCarthyism and anti-communist investigations at the local level. The author uses the case of Mary Knowles-a librarian who was investigated in the 1950s for alleged communist sympathies-to analyze how communities, local officials, and ordinary people were impacted by the politics surrounding the Cold War.